PP25 Activities and experiences of medical student first responders: a mixed methods study. Issue 9 (23rd August 2022) - Orsi, Andrew; Watson, Adam; Botan, Vanessa; Wijegoonewardene, Nimali; Lloyd, Dylan; Dunbar, Nic; Asghar, Zahid; Siriwardena, Aloysius Niroshan
Abstract : Background: Medical Student First Responder (MSFR) schemes provide a Community First Responder (CFR) resource to their local ambulance Trust and experience for students. We aimed to investigate the contribution of these schemes and perceptions of students taking part in them. Methods: In this convergent mixed methods study, we analysed dispatch data from two regional ambulance services and used propensity score matching to adjust for rurality and timing of attendance. MSFR attendances were compared with CFR and ambulance attendances. Multinomial logistic regression identified predictors of MSFR attendance compared with CFR and ambulance staff whilst accounting for confounders. We combined this with semistructured interviews of MSFRs from five schemes across the two regions. Interviews were transcribed verbatim and analysed using the Framework approach supported by NVivo. Final themes and categories were agreed through consensus. Results: We included MSFR attendances from 2019 (n = 5817). MSFRs were more likely to attend urgent category 1 and 2 calls (vs ambulance category 3: RRR 4.67, 95%CI 3.08 - 7.07 or category 4: RRR 8.85, 95%CI 1.09 - 71.75) and cardiorespiratory (vs ambulance RRR 0.44, 95%CI 0.35 - 0.56) or neurological/endocrine calls (vs ambulance RRR 0.55, 95%CI 0.41 - 0.74). MSFRs were more likely, compared to CFRs and ambulance staff, to be dispatched to younger patients, those from ethnic minorities and deprived areas. We interviewed 16 MSFRs from 5 medical schools. Participants described routes, requirements and challenges to recruitment. Training, mentorship, shadowing and debriefing were helpful to the role. Despite the risks and stress, most MSFRs enjoyed and valued their experience for enhancing clinical knowledge and skills in emergency care and understanding the wider context of care delivery. MSFRs' experience also helped prepare for a future career involving emergency care. Conclusions: MSFR schemes provide a valuable contribution to prehospital care and beneficial experiences for medical students.